The clockwerk / Noorzalyla Mokhtar … [et al.] - Mokhtar, Noorzalyla; Jamaludin, Mohd Hishamuddin; Mohd. Amin, Mohd. Shah Iskandar; Muhamad Faizul Tan, Faisal Tan; Azih, Muhammad Hisyam; Mustakim, Nurul Ain; Sauid, Muna Kameelah; Ebrahim, Zarina Begum; Zulkapli, Nurhafizah; Syed Yusoff, Syed Musakazim (Division of Research and Industry Linkages, 2017)
This product will help assist in teaching and learning of children with Autism to recognize time.